Combining thermocompression, multi-enzymolysis, and citric acid-grafting or carboxymethylation on the physicochemical and hypoglycemic properties of Ziziphus jujuba pit dietary fiber - Song, Xinling; Yang, Yong; Feng, Chen; Long, Peiyao; Li, Yan; Ma, Biao; Meng, Xinyue; Niu, Yueyue; Li, Yaqi (Frontiers in Nutrition, 2025)
IntroductionRed jujube (Ziziphus jujuba Mill.) pits are a rich, available, and inexpensive dietary fiber resource. However, red jujube pits are rarely used in the food industry because of their hardness and high content of cellulose and lignin.MethodsHerein, the influences of combining thermocompression, enzymolysis, citric acid-grafting, or carboxymethylation on the physicochemical and hypoglycemic properties of jujube pit dietary fiber (JPDF) were investigated.Results and discussionA lower crystallinity, more porous microstructure, smaller particle size, higher viscosity, expansion volume, and ability to retain water were observed in JPDF after thermocompression and enzymolysis combined with citric acid-grafting or carboxymethylation (P < 0.05). JPDF modified via thermocompression, enzymolysis, and carboxymethylation (JPDF-TEC) exhibited the largest surface area (189.21 m2·kg−1), highest viscosity (16.31 cP), expansion volume (8.70 ml/g), glucose diffusion-inhibitory activity (46.63%), and α-glycosidase-inhibitory activity (20.35%). Moreover, JPDF modified via thermocompression, enzymolysis, and citric acid-grafting (JPDF-TECA) exhibited the highest soluble fiber content (24.00 g/100 g), glucose sorption quantity (34.79 μmol·g−1), and α-amylase-inhibitory activity (23.43%). However, thermocompression and enzymolysis, coupled with citric acid-grafting or carboxymethylation, reduced the lightness of JPDF. Thus, thermocompression and enzymolysis, coupled with carboxymethylation, was the most effective method for improving the hypoglycemic properties and applications of JPDF.